Increased levels of Aβ42 decrease the lifespan of ob/ob mice with dysregulation of microglia and astrocytes. Issue 2 (16th December 2019) - Shinohara, Mitsuru; Tashiro, Yoshitaka; Shinohara, Motoko; Hirokawa, Junko; Suzuki, Kaoru; Onishi‐Takeya, Miyuki; Mukouzono, Masahiro; Takeda, Shuko; Saito, Takashi; Fukumori, Akio; Saido, Takaomi C.; Morishita, Ryuichi; et al.
Abstract: Clinical studies have indicated that obesity and diabetes are associated with Alzheimer's disease (AD) and neurodegeneration. Although the mechanisms underlying these associations remain elusive, the bidirectional interactions between obesity/diabetes and Alzheimer's disease (AD) may be involved in them. Both obesity/diabetes and AD significantly reduce life expectancy. We generated App NL‐F/wt knock‐in; ob/ob mice by crossing App NL‐F/wt knock‐in mice and ob/ob mice to investigate whether amyloid‐β (Aβ) affects the lifespan of ob/ob mice. App NL‐F/wt knock‐in; ob/ob mice displayed the shortest lifespan compared to wild‐type mice, App NL‐F/wt knock‐in mice, and ob/ob mice. Notably, the Aβ42 levels were increased at minimum levels before deposition in App NL‐F/wt knock‐in mice and App NL‐F/wt knock‐in; ob/ob mice at 18 months of age. No differences in the levels of several neuronal markers were observed between mice at this age. However, we observed increased levels of glial fibrillary acidic protein (GFAP), an astrocyte marker, in App NL‐F/wt knock‐in; ob/ob mice, while the levels of several microglial markers, including CD11b, TREM2, and DAP12, were decreased in both ob/ob mice and App NL‐F/wt knock‐in; ob/ob mice. The increase in GFAP levels was not observed in young App NL‐F/wt knock‐in; ob/ob mice. Thus, the increased Aβ42 levels may decrease the lifespan of ob/ob mice, which is associated with the dysregulation of microglia and astrocytes in an age‐dependent manner. Based on these findings, the imbalance in these neuroinflammatory cells may provide a clue to the mechanisms by which the interaction between obesity/diabetes and early AD reduces life expectancy.